2012
DOI: 10.1039/c2cp43370b
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Simple Infiltrated Microstructure Polarization Loss Estimation (SIMPLE) model to describe the performance of nano-composite solid oxide fuel cell cathodes

Abstract: Nano-composite Sm(0.5)Sr(0.5)CoO(3-δ) (SSC)-Ce(0.9)Gd(0.1)O(1.95) (GDC) and La(0.6)Sr(0.4)Co(0.8)Fe(0.2)O(3-δ) (LSCF)-GDC Solid Oxide Fuel Cell (SOFC) cathodes with various infiltrate loading levels were prepared through multiple nitrate solution infiltrations into porous GDC ionic conducting (IC) scaffolds. Microstructural analyses indicated that the average SSC and average LSCF hemispherical particle radii remained roughly constant, at 25 nm, across multiple infiltration-gelation-firing sequences. Comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
66
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 61 publications
12
66
0
Order By: Relevance
“…In all cases, measurements taken with AC amplitudes of 25 and 50 mV yielded identical impedance curve shapes, and the general shape of the impedance curves were consistent with those observed previously in the literature for LSF-LSC infiltrated ceria. 9,[13][14][15]20,21 For electrodes fabricated with a particular infiltration method, Figure 1 shows that the electrode resistance systematically decreases as the infiltrate Co:Fe ratio increases. This behavior is consistent with previous literature studies showing that at typical SOFC operating temperatures the oxygen surface exchange resistance (Rs) of materials within the LSC-LSF solid solution decrease as the Co:Fe ratio increases, 17,18,[22][23][24] and suggests that oxygen surface exchange is a dominant source of resistance in these cathodes at 600…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, measurements taken with AC amplitudes of 25 and 50 mV yielded identical impedance curve shapes, and the general shape of the impedance curves were consistent with those observed previously in the literature for LSF-LSC infiltrated ceria. 9,[13][14][15]20,21 For electrodes fabricated with a particular infiltration method, Figure 1 shows that the electrode resistance systematically decreases as the infiltrate Co:Fe ratio increases. This behavior is consistent with previous literature studies showing that at typical SOFC operating temperatures the oxygen surface exchange resistance (Rs) of materials within the LSC-LSF solid solution decrease as the Co:Fe ratio increases, 17,18,[22][23][24] and suggests that oxygen surface exchange is a dominant source of resistance in these cathodes at 600…”
Section: Resultsmentioning
confidence: 99%
“…Based on the definition of resistance, ohmic resistivity (ρ Ohmic ) values for each cell were determined by dividing the high-frequency Nyquist plot x-axis intercept by the electrolyte thickness and multiplying by the electrode's geometric area (0.5 cm 2 ). To help understand the observed performance trends, R P predictions were made using a previously-described 8,9,12 Simple Infiltrated Microstructure Polarization Loss Estimation (SIMPLE) model that accounts for electrical losses associated with oxygen exchange into the MIEC infiltrate and oxygen conduction through the GDC scaffold. Specifically, SIMPLE Model Rp predictions were made by inputting 1) La 0.6 Sr 0.4 Fe y Co 1-y O 3-x densities from the Joint Committee on Powder Diffraction Standards (JCPDS) database, 16 2) the MIEC infiltrate loading levels, cathode thicknesses, geometric cathode areas, cathode porosities, MIEC nano-particle diameters, and GDC scaffold column widths stated in Table I, 3) the GDC scaffold ionic conductivity from Nicholas et al, 9 4) the LSF, LSFC, and LSC oxygen surface exchange resistances (Rs) from Baumann et al, 17 5) the LSCF Rs from Xiong et al, 18 and 6) the LSCF55 Rs obtained by averaging the LSF and LSC Rs values from Baumann et al 17 into the SIMPLE model spreadsheet available at https://www.egr.msu.edu/nicholasgroup/simple.php.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Shah et al 4 first reported that the infiltrated LSCF nanoparticles on the GDC backbone surface are hemispheres. Recently, Nicholas et al 13 reported that the infiltrated Sm 0.5 Sr 0.5 CoO 3-δ nanoparticles on the GDC backbone surface were also hemispherical. Fig.…”
Section: Numerical Infiltration Methodologymentioning
confidence: 99%
“…5 neglects the resistance of backbone structure, while the recently proposed SIMPLE model by Nicholas et al considered it. 13 Thus the SIMPLE model is also used for validation. The reported parameters from the literature are used for model validation.…”
Section: Journal Of Thementioning
confidence: 99%
See 1 more Smart Citation